MTHFR gene variants and non-MALT lymphoma development in primary Sjogren’s syndrome - Sofia Fragkioudaki (Nature Portfolio, 2017)
Abstract Primary Sjogren’s syndrome (pSS) confers increased risk for non-Hodgkin lymphoma (NHL) development. Two common polymorphisms, the c. 677C > T and c. 1298A > C, of the methylene-tetrahydrofolate reductase (MTHFR) gene, an enzyme essential in DNA synthesis and methylation, have been associated with susceptibility to NHL. Herein, we tested the hypothesis that MTHFR variants contribute to pSS-related lymphomagenesis. 356 pSS patients, of whom 75 had MALT and 19 non-MALT NHL and 600 healthy controls were genotyped for the detection of MTHFR polymorphisms. DNA methylation levels were assessed by pyrosequencing of the LINE-1 retroelement promoter in DNA from 55 salivary gland tissues from pSS patients. DNA double-strand breaks were determined in peripheral blood mononuclear cells from 13 pSS patients, using comet assay. Αnalysis according to lymphoma subtype revealed increased frequency of c. 677C > T TT genotype and T allele, as well as reduced prevalence of the c. 1298A > C C allele in the pSS non-MALT group compared to controls and patients without NHL. MTHFR c. 677C > T TT genotype was associated with reduced DNA methylation levels, while MTHFR c. 1298A > C AC genotype with reduced DNA double-strand breaks levels. MTHFR variants may be involved in SS non-MALT NHL development, through contribution to defective DNA methylation and genomic instability.